PREVALÊNCIA OF ALTERATIONS POSTURAIS BETWEEN BEGINNINGS IN THE PRACTICAL ONE OF ACTIVITY PHYSICS IN AN ACADEMY OF SÃO JOÃO DEL REI-MG. (Fiep Bulletin - online, 2015)
The population each time more comes being attack with some posturais alterations and these they provoke physical problems serious comprometedores in the quality of life. The objective of this study is to evidentiary the main posturais alterations between the beginning ones in the practical one of physical activities of an academy in São João Del Rei, MG in the period of July the December of 2004. This study propose to verify it which posturais elements they must be presented giving one it has supported specific and fidgeting for the one accomplishment program ergonomicamente elaborated. A collection was carried through initially of data in the Apollo Academy of São João Del Rei, MG in a group of 700 pupils beginning in the physical activity, with the average age of 28 years, of the sort feminine masculine and that if they had submitted to the physical and posturais evaluations. It was used the system of physical evaluation computerized PHISYCAL TEST 4.2. The evaluation it was carried through to leaving of the inferior members for the superiors having segmentation in accordance with the anatomical regions, as feet, knees, hips, trunk, shoulders and neck. The visual inspections had been carried through in such a way in the plan sagittal how much in the plans frontal, dorsal and in the position antero-flexion. Results gotten with the carried through study had evidenced that 100% of the evaluated ones they had presented alterations in posturais shunting lines. Scoliosis was found in 56,8% of evaluations, being convex 38.1% right and convex 18.7% the left, hiperlordose in 28,1% and hipercifose in 17,8%. It was observed that the factors preponderant for a bigger number of these shunting lines they had been that in almost its totality the evaluated people was of age enters the 14 28 years, sedentary rights hand and. One concluded that programs and evaluations of orientation e immediate intervention, periodic and corrective, is preponderant factors stops the prevention and improves significant of posturais shunting lines and quality of life, making possible thus a good corporal biomechanics, using itself of the ergonomics in the accomplishment of exercises.
Keywords: evaluation posturais; sedentary postural; shunting lines.